ZnXFe3-xO4 (0.01 ≤ x ≤ 0.8) nanoparticles for controlled magnetic hyperthermia application - Srivastava M.; Alla S.K.; Meena S.S.; Gupta N.; Mandal R.K.; Prasad N.K. (My University, 2025)
The ferrofluids based on ZnxFe3-xO4 (0.01 ≤ x ≤ 0.8) nanoparticles have shown stabilization near therapeutic temperature (∼42 °C) in the presence of external AC magnetic fields similar to that of tetravalent ion substituted magnetites. These nanoparticles were prepared using microwave refluxing technique. Rietveld analysis of X-ray diffraction patterns of the as prepared samples confirmed their single phase mixed spinel type structure. It further suggests that all the Zn2+ ions occupy tetrahedral voids. The spherical shaped particles had sizes in the range of 3-10 nm, as observed under transmission electron microscopy. X-ray photoelectron spectra have confirmed the presence of Fe2+, Fe3+ and Zn2+ ions in the samples. The Zn0.2Fe2.8O4 sample displayed the highest saturation magnetization value (∼65 A m2 kg-1) amongst all the samples. As the concentration of Zn increased, beyond x > 0.3, the value of saturation magnetization continuously diminished due to the dominance of the nonmagnetic ion. Fe2+ ions occupying both the sites was confirmed from room temperature Mössbauer spectroscopy. © 2018 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.